KOMUNIKASI PROFETIK DI MEDIA SOSIAL DALAM KONFLIK PALESTINA ISRAEL - Wulandari, Tresia; Candra, Muhammad Fazri (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
Abstract: Prophetic communication is a framework for new communication science practices from an Islamic communication perspective that combines general communication science concepts with religious philosophy by emphasizing two aspects of meaning, namely the dissemination of information that contains truth and good meaning, and the delivery of information that is carried out appropriately and politely. Social media is one of the technological advances that is used to disseminate information, one of which is the spread of fake news about the conflict between Palestine and Israel which violates the media code of ethics and Islamic values ​​which are interpreted through prophetic communication. The researchers will study in more depth using qualitative research methods, data collection techniques through in-depth interviews with Palestinian residents. The results state that Instagram and Facebook are the social media that contain the most fake news, one of which is accusing Hamas of being a terrorist because it carried out attacks on the Zionists, thus triggering various perspectives from the public without them knowing how cruel the Zionists were in attacking Palestinians for seven years. The large number of fake news about Hamas means that we as Muslims have to filter and validate news sources according to reality. Because many media distort facts which are considered very confusing to the public. Thus, the presence of social media as a new media from a prophetic communication perspective has pros and cons, including being able to build solidarity among Muslims in fighting colonialism and there is still a lot of fake news packaged in such a way that it is able to make the audience believe the news.